KAJIAN SIMULASI COMPUTATIONAL FLUID DYNAMICS POLA ALIRAN AIR DALAM TURBIN VORTEX PADA VARIASI SUDUT TAKIK - Danus, Ishak; Suarda, Made; Sukadana, I Gusti Ketut (Teknik Desain Mekanika, 2024)
Abstract Vortex turbines are a type of renewable energy technology by utilizing water as a source of energy. Vortex turbines can be used in areas that have heads ranging from 0.7m. Research and development of Vortex Turbines began in 2004. notch angle is an important parameter that affects the performance of Vortex Turbines. The method used in this research is computational fluid dynamic simulation by varying the notch angle in the canal. This study was conducted to determine the water flow pattern which includes velocity contours and pressure contours and Vortex Turbine performance which includes torque, output power and efficiency. The results obtained show that the velocity contour is inversely proportional to the pressure contour. The speed value is directly proportional to the greater the notch angle, while the pressure value is inversely proportional to the greater the notch angle. The highest efficiency is found in the 15 ° notch angle variation of 6.11% while the lowest efficiency is found at a notch angle of 7 ° with an efficiency value of 2.69%. Keywords: Computational Fluid Dynamic, Vortex turbine, Notch Angle, Flow Pattern, Turbine Performance